L’instabilité politique en Polynésie française - Sémir Al Wardi (EchoGéo)
Electoral system, weakness of ideology et party-switching may account for such an instability in French Polynesia. Party-Switching is an element of the Polynesian political culture: the Polynesian representatives have often thought that they were free to dispose of their mandate as they wished and so, that they could form a partnership with any political party once they had been elected.